Paeoniflorin, a Natural Product With Multiple Targets in Liver Diseases—A Mini Review - Ma, Xiao; Zhang, Wenwen; Jiang, Yinxiao; Wen, Jianxia; Wei, Shizhang; Zhao, Yanling (Frontiers in Pharmacology, 2020)
Paeoniflorin is derived from Paeonia suffruticosa Andr., Paeonia lactiflora Pall. or Paeonia veitchii Lynch and has been used in traditional medical applications for more than 2000 years. Paeoniflorin is a monoterpenoid glycoside with various effects on liver diseases. Recent studies have revealed that paeoniflorin demonstrates a wide range of activities, including hepatic protection, cholestasis alleviation, liver fibrosis attenuation, nonalcoholic fatty liver disease prevention and hepatocellular carcinoma inhibition involved in multiple pathways. Moreover, anti-inflammation, antioxidation and immune regulation with the regulation of TLR4-NF‐κB, ROCK/NF-κB, HO-1, mitochondria-dependent as well as HMGB1‐TLR4 signaling pathways are correlated with hepatic protection in liver injury and nonalcoholic fatty liver disease. Antioxidative mechanisms, anti-inflammation and hepatic transporter regulation involved in NOX4, PI3K/Akt/Nrf2, NF‐κB, NTCP, BSEP as well as MRP2 signals are mainly relevant to the anticholestatic effect of paeoniflorin. The inhibition of hepatic stellate cell activation, alleviation of extracellular matrix deposition via vast signals such as mTOR/HIF-1α, TGF-β1/Smads, JAK2/STAT6 are primarily involved in the antifibrotic effect of paeoniflorin. The regulation of macrophages also contributes to the alleviation effect on liver fibrosis. In addition, the reduction of invasion, metastasis, and adhesion and the induction of apoptosis-related targets , including Bax, Bcl-2, and caspase-3, are related to its effect on hepatocellular carcinoma. The literature indicates that paeoniflorin might have potent efficacy in complex liver diseases and demonstrates the profound medicinal value of paeoniflorin.